Sistem Monitoring Tanaman Sawi Di Lingkungan Greenhouse Menggunakan Catu Daya Surya Panel - Sunardi; Riskiana; Jamal A. Rachman Saprin; Toto Raharjo; Aris Suryadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Cultivation of mustard plants (Brassica rapa var. parachinensis L.) in open land has many obstacles such as pest attacks, wind, floods, environmental temperature, to watering problems that do not meet the requirements of plant growth, the impact is the disruption of plant growth. Cultivation of plants in the greenhouse is a good alternative to control these constraints. However, the need for electricity for both industry, offices, and the general public and individuals is greatly increased. However, this increase in electricity needs is not accompanied by the addition of electricity supply. Based on these problems, solar energy is chosen as an alternative energy to produce electrical energy. The tool used in this study is solar panels with a capacity of 50 Watt Peak. In order for solar energy to be used at night, during the day the electricity generated is stored first to the battery with a capacity of 20 Ampere Hour. Mustard plant monitoring system in greenhouse environment has been designed using Arduino Uno microcontroller. Control is developed using two sensors namely DHT11 sensor and soil moisture sensor. Using two actuators namely fan actuator and water pump actuator as environmental temperature and humidity control. The design is placed inside a plant house connected to the LCD as a data viewer during the cultivation period